O objeto transicional pode ser uma pessoa? teoria e clínica - Migliorini, Walter José Martins [UNESP] (2014)
The objective of this work is to answer the question posed in the title, based on the texts of D. W. Winnicott. To this effect we addressed the origins of the concept of transitional object in the author’s work, the chronology of its first appearances, direct references to the topic and a discussion of a clinical case. Winnicott rarely referred to a person as being another person’s transitional object, and when he did so, he situated this experience in the field of pathology, and when referring to it, used such terms as “comforter object”, “fetish object” and “regressive object”. In contrast, the concept of transitional object is linked to an experience indicative of mental health, of transition between fusion and mother-baby separation, and of the personal and symbolic use of objects of the sensory field. Maintaining this conceptual specificity enables us to discriminate nuances in the evolution of the use of material objects by the child, and helps to guide anamnesis, diagnosis and the therapeutic process.